Smart Tourism Studies from an Axiological Perspective - Purwaningsih, Mardiana; Ekosiwi, Embun Kenyowati (Prasetiya Mulya Publishing, 2019)
The concept of Smart Tourism was built to take advantage of the development of IT in the tourism industry and provide added value for environmental sustainability. IT is proven to encourage tourism publication easily, but allows excessive exploitation of the environment, as well as causing other ethical and aesthetic problems. Symptoms of ethical deterioration and aesthetic changes due to digital engineering encourage a study to be carried out, with the aim of exploring the potential deviations of IT from the original development goals. The research method used is systematic content analysis of interdisciplinary literature with insight into axiology and philosophical issues in tourism and smart tourism applications such as social media, data science, and IoT. Social media users often only focus on self-presentation and not think to be environmentally responsible. As a result, there was a lot of damage to tourism objects which eventually became viral in cyberspace. The disclosure of personal data on social media that is actually done consciously by the owner also poses a threat to privacy and illegal actions in using information. So, word